Biomechanical effects of medial osteoarthritis progression and UKA on knee lateral compartment using fibril-reinforced biphasic material in finite element study - Jing Zhang; Weijian Lin; Junyan Li; Zhenxian Chen; Zhongmin Jin (Scientific Reports)
Abstract The potential risks of osteoarthritis (OA) progression in the lateral compartment during the progression of medial knee OA and after medial unicompartmental knee arthroplasty (UKA) remain to be elucidated. Thus, five medial knee OA models with different progression stages and one medial UKA model were established using the finite element method to investigate the biomechanical differences of lateral compartment articular cartilage (AC). The AC and meniscus were constructed by fibril-reinforced biphasic material, and the real biphasic contact conditions were adopted. The results showed that biomechanical differences in lateral compartments were within 2% between the healthy knee model (OARSI 0–1) and early medial knee OA models (OARSI 2–3). However, in advanced medial knee OA (OARSI 4.5), up to a 7.0% increase in stress and a 22.2% increase in a strain of the lateral compartment AC were predicted. After medial UKA surgery, the maximum shear strain of the lateral compartment AC was reduced by about 22.2% when compared with advanced medial knee OA. In conclusion, the progression of medial knee OA may cause OA development in the lateral compartment. In contrast, medial UKA surgery might help to lower the risks of OA progression in the lateral compartment when in the advanced medial knee OA stage.